Gender-Diverse Audit Committees, Size of Public Accounting Firms, and Audit Opinions on Stock Prices Mediated by Audit Report Lag - Zalisman Rahmadan; Yuliusman; Rita Friyani; Achmad Hizazi; Muhammad Gowon (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research examines and assesses the connection between gender-diverse audit committees, the size of public accounting firms, and audit opinions on stock price mediated by audit report lag. The research topic explored energy companies listed on the Indonesian stock exchange (IDX). Fifty-four data from three years of observation were included The research sample was selected with a purposive sampling technique, following three particular criteria. Data were analyzed using PLS-SEM analysis. Data processed using SmartPLS 3.2.9 application. The results of the tests showed that results were Gender-diverse audit committees did not affect Audit Report Lag. In contrast, the size of the public accounting firm and audit opinion affected the audit report lag. Gender-diverse audit committees had no direct and indirect effect on stock prices. In contrast, the public accounting firm's size and audit opinion affect stock prices directly and indirectly, and audit report lag affects stock prices.